2021
DOI: 10.1002/dmrr.3466
|View full text |Cite
|
Sign up to set email alerts
|

Switching from insulin to dulaglutide therapy in patients with type 2 diabetes: A real‐world data study

Abstract: Aim Patients with type 2 diabetes (T2DM) who require injectable therapy have been conventionally treated with insulin. A glucagon‐like peptide 1 receptor agonist was recently recommended as first‐line injectable treatment, but few studies have investigated the effects of switching from insulin to dulaglutide. This study investigated the clinical efficacy and parameters affecting responses to dulaglutide as an alternative to insulin in patients with T2DM in a real‐world clinical setting. Methods Ninety‐eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Second, we found that older age, a higher dose of insulin at the time of switching to dulaglutide, and a low level of postprandial glucose were significant predictive factors for insulin resumption after switching from insulin to weekly dulaglutide. Previous studies have investigated the effectiveness of switching from insulin to dulaglutide in reducing HbA1c levels and body weight in patients with T2D (16). In contrast to our study, the patients used a lower dose of insulin (about 20U/day), and approximately 94% of the enrolled patients used only basal insulin with OHAs.…”
Section: Discussionmentioning
confidence: 77%
“…Second, we found that older age, a higher dose of insulin at the time of switching to dulaglutide, and a low level of postprandial glucose were significant predictive factors for insulin resumption after switching from insulin to weekly dulaglutide. Previous studies have investigated the effectiveness of switching from insulin to dulaglutide in reducing HbA1c levels and body weight in patients with T2D (16). In contrast to our study, the patients used a lower dose of insulin (about 20U/day), and approximately 94% of the enrolled patients used only basal insulin with OHAs.…”
Section: Discussionmentioning
confidence: 77%
“…People with T2D who do not achieve recommended glycemic targets may eventually require treatment intensification with insulin or a glucagon-like peptide-1 receptor agonist (GLP-1 RA), such as dulaglutide, or the gastric inhibitory peptide (GIP) and GLP-1 dual receptor agonist, tirzepatide [ 11 ]. Choice of glucose-lowering agents in T2D should be guided by clinical considerations (e.g., presence or high risk of cardiovascular disease, heart failure, chronic kidney disease, and hypoglycemia), side effect profiles of medications, contraindications, and individual preferences [ 12 ].…”
Section: Introductionmentioning
confidence: 99%